Plankton and marine aggregates as transmission vectors for V. aestuarianus 02/041 infecting the pacific oyster Crassostrea gigas - Doni L.; Tassistro G.; Oliveri C.; Balbi T.; Auguste M.; Pallavicini A.; Canesi L.; Pruzzo C.; Vezzulli L. (Environmental Microbiology Reports, 2023)
Vibrio aestuarianus is a bacterium related to mass mortality outbreaks of the Pacific oyster, Crassostrea gigas in Europe. In this study, the role of different planktonic substrates (phytoplankton cells, marine aggregates and chitin fragments) in mediating V. aestuarianus 02/041 infection of oysters was evaluated by controlled infection experiments. It was shown that phytoplankton cells and, to a greater extent, marine aggregates, significantly promote V. aestuarianus 02/041 intake by C. gigas maintained under stressful conditions in the laboratory. Such intake is associated with higher concentration of the pathogen in the bivalve hemolymph and compromised health status of infected oysters. In contrast, chitin particles do not play a significant role as transmission vector for V. aestuarianus 02/041 infecting its bivalve host. Interestingly, incorporation into marine aggregates foster extracellular proteases (ECPs) activity and a higher expression of bacterial virulence genes, that are potentially involved in bivalve infection. Results from this study contribute to elucidate transmission patterns of V. aestuarianus 02/041 to C. gigas that may be useful for the development of efficient measures to prevent and control oyster disease outbreaks.